Karakteristik Bahan Bakar Pelet Jerami Padi: Pengaruh Ukuran Partikel dan Penambahan Bekatul - Triandini, Heryanti Nur; Haryanto, Agus; Rahmawati, Winda (abe.fp.unila.ac.id, 2022)
Rice straw is a potential agricultural waste biomass for alternative energy sources in the form of pellets. This study aimed to determine the effect of particle size and the addition of rice bran on the characteristics of rice straw pellets. The study was arranged in a completely randomized design with two factors. The first factor was the particle size with four levels, namely P1 (passed a 25 mesh sieve), P2 (between 10 and 25 mesh), P3 (did not pass 10 mesh), and P4 (not sieved). The second factor was the addition of bran which consisted of B0 (0%), B1 (5%), B2 (10%), and B3 (15%). All treatment combinations were carried out with 3 replications. Parameters observed includeded moisture content, ash content, density, and pellet strength. Rice straw has a calorific value of 17.96 MJ/kg so it is potential as a fuel. The results showed that the particle size and the addition of rice bran significantly affected the parameters of moisture content, density, and pellet strength. Moisture content, density, and strength (durability) of pellets increased with decreasing particle size. The addition of rice bran showed inconsistent effects: it increased the strength of the pellets but decreased the density of the pellets. Good rice straw pellets were obtained from fine (passing 25 mesh) to medium (between 10 to 25 mesh) sized particles.